2019
DOI: 10.3390/medicina55070385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression in Sickle Cell Disease Hospitalization-Related Outcomes: An Analysis of the National Inpatient Sample (NIS)

Abstract: Objectives: This study aimed to analyze and discern the differences in demographics and inpatient outcomes (length of stay (LOS), total charges, disease severity, and mortality) between depressed versus non-depressed sickle cell disease (SCD) patients. Materials and Methods: A retrospective analysis was conducted using the Nationwide Inpatient Sample (2010–2014). We identified 73,225 SCD hospitalizations and comorbid depression (6317, 8.6%) as the primary and the other diagnosis, respectively, using Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Our study may be underestimating the real number of patients with depression due to the underdiagnose and lack of registry of depression in the context of an acute hospitalization. These constraints have also been identified in previous studies using similar methodologies and settings 19‐21 …”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our study may be underestimating the real number of patients with depression due to the underdiagnose and lack of registry of depression in the context of an acute hospitalization. These constraints have also been identified in previous studies using similar methodologies and settings 19‐21 …”
Section: Discussionsupporting
confidence: 63%
“…These constraints have also been identified in previous studies using similar methodologies and settings. [19][20][21] Moreover, an increase of registered depression was found throughout the study period. The increased quality of hospital-coded data in Portugal throughout the years may explain this results.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study aimed to determine the prevalence and identify the relationship of sociodemographics with depression and anxiety of SCD patients at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Other researches found that depressed patients will have significantly higher health care utilization and inpatient costs than nondepressed patients [17][18][19]. So determining the risk factors that increase a psychological disorder in SCD patients will be a chance to decrease the cost and provide much better medical care to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant differences in socioeconomic status between disease groups, poverty, education, and employment status were not associated with odds of mood disorders. Another study of adults with SCD also found that income and other socioeconomic factors did not have an impact on mental health 62 . More data confirming this finding are needed, but for Black Americans, future studies may find that chronic illness and related biological and psychosocial risk factors are greater contributors to mental health than socioeconomic factors.…”
Section: Discussionmentioning
confidence: 93%